International Rickettsia Disease Surveillance: An Example of Cooperative Research to Increase Laboratory Capability and Capacity for Risk Assessment of Rickettsial Outbreaks Worldwide - Jiang, Ju; Farris, Christina M.; Yeh, Kenneth B.; Richards, Allen L. (Frontiers in Medicine, 2021)
Cooperative research that addresses infectious disease surveillance and outbreak investigations relies heavily on availability and effective use of appropriate diagnostic tools, including serological and molecular assays, as exemplified by the current COVID-19 pandemic. In this paper, we stress the importance of using these assays to support collaborative epidemiological studies to assess risk of rickettsial disease outbreaks among international partner countries. Workforce development, mentorship and training are important components in building laboratory capability and capacity to assess risk of and mitigate emerging disease outbreaks. International partnerships that fund cooperative research through mentoring and on the job training are successful examples for enhancing infectious disease surveillance. Cooperative research studies between the Naval Medical Research Center’s Rickettsial Diseases Research Program (RDRP) and 17 institutes from 9 countries among 5 continents were conducted since the early 2000s to address the presence of and the risk for endemic rickettsial diseases. To establish serological and molecular assays in the collaborative institutes, initial training and continued material and technical support were provided by RDRP. The methods used in the studies to detect and identify the rickettsial infections: 1) group-specific IgM and IgG serological assays and 2) molecular assays. Twenty-six cooperative research projects were conducted, which enhanced capability and capacity of 17 research institutes to estimate risk of rickettsial diseases. These international collaborative studies led to the recognition and/or confirmation of rickettsial diseases within each of the countries. Moreover, with the identification of specific pathogen and non-pathogen Rickettsia species a more accurate risk assessment could be made in surveillance studies using environmental samples. The discoveries from these projects were not only benefited the host countries but were also laid out to the rest of the world through presentations at international scientific meetings (n=40) and peer-reviewed publications (n=18). The cooperative research studies conducted in multiple international institutes led to the incorporation of new SOPs and trainings for laboratory procedures, biosafety, biosurety and biosecurity methods, and performance of rickettsia-specific assays and identification of known and unknown rickettsial agents by introduction of new serologic and molecular assays that complemented traditional microbiology methods.